2013
DOI: 10.1186/2050-7283-1-26
|View full text |Cite|
|
Sign up to set email alerts
|

Listen protect connect for traumatized schoolchildren: a pilot study of psychological first aid

Abstract: BackgroundListen Protect Connect (LPC), a school-based program of Psychological First Aid delivered by non-mental health professionals, is intended to support trauma-exposed children. Our objective was to implement LPC in a school setting and assess the effectiveness of LPC on improving psychosocial outcomes associated with trauma.MethodsA pilot quasi-experiment was conducted with middle school children self-identified or referred to the school nurse as potentially exposed to stressful life experiences. LPC wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 38 publications
0
55
0
6
Order By: Relevance
“…As seen in Table , of the 41 studies, 7 studies examined miscellaneous interventions (Psychodrama Group: Carbonell & Parteleno‐Barehmi, ; Unnamed Intervention: C. M. Chemtob, Nakashima, & Hamada, ; Project SHIFA: Ellis et al, ; Expressive Writing Intervention: Giannotta et al, ; Adolescent Grief and Loss Group: Malone, ; Journey of Hope: Powell & Thompson, ; Listen, Protect, Connect: Ramirez et al, ). Of the seven studies, only Giannotta et al () expressive writing intervention did not find statistically different changes in student outcome scores.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table , of the 41 studies, 7 studies examined miscellaneous interventions (Psychodrama Group: Carbonell & Parteleno‐Barehmi, ; Unnamed Intervention: C. M. Chemtob, Nakashima, & Hamada, ; Project SHIFA: Ellis et al, ; Expressive Writing Intervention: Giannotta et al, ; Adolescent Grief and Loss Group: Malone, ; Journey of Hope: Powell & Thompson, ; Listen, Protect, Connect: Ramirez et al, ). Of the seven studies, only Giannotta et al () expressive writing intervention did not find statistically different changes in student outcome scores.…”
Section: Resultsmentioning
confidence: 99%
“…Although originally developed as a response to disasters, PFA provides a framework that has been applied to other personal adverse experiences such as interpersonal violence and family trauma (57). PFA identifies children and their caregivers immediately after a life stressor and provides information, education, comfort, and support, which results in acceleration of recovery, promotion of mental health, and increased resiliency (58,59). Recently, the World Health Organization published "Psychological first aid: Guide for field workers, " which describes crises ranging from "war to natural disasters, accidents, fires, and interpersonal violence. "…”
Section: Approaches To Reducing the Burden Of Acesmentioning
confidence: 99%
“…Adults trained in PFA report increased knowledge, skills, and self-efficacy in applying skills to support youth with histories of trauma (61,62). One study also reported PFA being effective in improving connectedness and stress among youth traumatized by a disaster, bullying, death or illness of a family member, or injury (59). Thus, PFA is an ideal program that may be delivered by all members of a trauma-informed organization, even by those without advanced mental health training.…”
Section: Approaches To Reducing the Burden Of Acesmentioning
confidence: 99%
“…On the other hand, with analytical and deliberate processing, PFA volunteers could express better reflective understandings of the victim by facilitating a "refractory mode" that activates areas of the frontal cortex (Farchi 2014, Ramirez et al 2013) and by providing a deliberate activation and conscious interpretation of the emotional reactions processes and behaviors of discomfort (Hafstad et al 2012); based on the acquisition of scheduled competencies or cognitive domains (McCabe et al 2014). Such conditions allow the victims return to the feeling of security under a framework of psycho educational preventive approach to PTSD.…”
Section: Discussionmentioning
confidence: 99%